ANALISIS KEBUTUHAN PEMBELAJARAN BAHASA INGGRIS MAHASISWA TEKNIK PERKALAPAN - Antika, Rindilla; Asfina, Risda (ABEC Indonesia, 2023)
Being an archipelagic country is a plus factor for Indonesia in various fields, including the economic field. One of the important qualities to support the development of maritime potential in Indonesia is the ability of English for the related fields (ESP). This study aims to find out the learning materials needed by students of the Department of Naval Architecture so that they acquire English skills that are relevant to their academic and work fields. This study will further develop teaching material in the form of problem-based learning (PBL) module. This study was a descriptive qualitative study using questionnaires and interviews for data collection. The respondents of this study were 50 students and 2 lecturers from the Department of Naval Architecture, Politeknik Negeri Bengkalis. This study found that the students of the Naval Architecture Department had the skills of listening, reading, speaking, writing, and pronunciation at the intermediate level. The skills really needed by the students of the Naval Architecture Department were listening and pronunciation. The topics needed by the students were Safety of Life at the Sea (SOLAS), Biro Klasisifikasi Indonesia (BKI), and English for job seekers. In addition, the PBL method is suitable and can be used in English classes for the Department of Naval Architecture.